The Long-Distance Teammate : Stay Engaged and Connected While Working Anywhere - Eikenberry, Kevin, 1962- (Berrett-Koehler Publishers, Inc., 2021)
"What does it mean to "go to work" when you don't actually leave the house? This is the ultimate guide for remote workers who want to stay engaged as team members, maintain robust work relationships, and keep an eye on their long-term career goals"--